A review of Industry 4.0 characteristics and challenges, with potential improvements using blockchain technology. (December 2021) - Aoun, Alain; Ilinca, Adrian; Ghandour, Mazen; Ibrahim, Hussein
Highlights: Main characteristics of Industry 4.0. The different technical, economic and social challenges and barriers facing a wide adoption of Industry 4.0. Blockchain supporting Industry 4.0 strategy. How blockchain can push forward the development of Industry 4.0. Abstract: Industry 4.0 mainly refers to factories in which machines use smart and autonomous systems enhanced by the Internet of Things (IoT), Artificial Intelligence (AI), machine learning and cyber-physical systems. But what reveals the true potential of Industry 4.0 is the established connection and communication between computers and machines that allow making decisions without any human intervention. The network formed by these interconnected machines, and the generated considerable amount of data, marks the actual value of Industry 4.0. Looking at the main features of Industry 4.0, we find many similarities with blockchain technology. The key drivers for Industry 4.0 and blockchain are data management, connectivity and digitization. Additionally, decentralization and distribution are considered as shared architectural features. This paper seeks to open new horizons on the potential of blockchain technology as an empowering tool for the 4th industrial era. We are first investigating the fundamentals of Industry 4.0, its challenges, barriers and limitations, and finally exploring areas where blockchain technology can bring new features and add value to the deployment of Industry 4.0.